Zakho from 11 March 1970 To 6 March of 1975: Historical - Political Study - Monir, Rojin Ch. (Humanities Journal of University of Zakho, 2017)
The Zakho areas from the period of 11 March to 6 March of 1975 had preponderant role in the history of the city itself and Kurdistan in general, and in particular of politic, society and economic. So this research, which is entitled “Zakho from 11 March to 6 March of 1975: historical study”, attempting to show the key events that occurred in this city. This study is contained of three sections. The first section is included the period of 11 March 1970 till 1974, in this period the city somehow was stable, peaceful and had more freedom. It is endeavor of this article to depict the attitude of the people of this city to the 11 March of 1970 Agreement, Idris Barzani visiting to the city and the killing attempt of the head of the Kurdistan Democratic Party Mullah Mustafa Barzani. Further, it shows the attitude of the people of city to the murder of sub-governorate of Sinjar mayor. The second section of this research shows the road way of war, which occurred between the Iraqi government and the leader of Kurdish revolution in 1974, in particular the war of Gali “narrow of Zako” in addition to its consequence on the citizen of this city, which imposed them to fled to surrounding villages, mountains, likewise, some were ended up to the neighboring countries namely Iran, Turkey, Syria and European states fearing of the central government mistreatment. Finally, this study illustrates the central government campaign of controlling of the city, the economic sanction and social implication of that policy of central government imposed. The three section of this research shows the most important political and military organizations in this city, specifically the Kurdistan Democratic Party and the Iraqi Communist Party.